Association Between Myocardial Injury and Cardiovascular Outcomes of Orthopaedic Surgery: A Vascular Events in Noncardiac Surgery Patients Cohort Evaluation (VISION) Substudy. (20th May 2020) - Thomas, Sabu; Borges, Flavia; Bhandari, Mohit; De Beer, Justin; Urrútia Cuchí, Gerard; Adili, Anthony; Winemaker, Mitchell; Avram, Victoria; Chan, Matthew T.V.; Lamas, Claudia; Cruz, Patricia; Aguilera, Xavier; et al.
Abstract : Background: Myocardial injury after noncardiac surgery (MINS) is common and of prognostic importance. Little is known about MINS in orthopaedic surgery. The diagnostic criterion for MINS was a level of ≥0.03 ng/mL on a non-high-sensitivity troponin T (TnT) assay due to myocardial ischemia. Methods: We undertook an international, prospective study of 15, 103 patients ≥45 years of age who had inpatient noncardiac surgery; 3, 092 underwent orthopaedic surgery. Non-high-sensitivity TnT assays were performed on postoperative days 0, 1, 2, and 3. Among orthopaedic patients, we determined (1) the prognostic relevance of the MINS diagnostic criteria, (2) the 30-day mortality rate for those with and without MINS, and (3) the probable proportion of MINS cases that would go undetected without troponin monitoring because of a lack of an ischemic symptom. Results: Three hundred and sixty-seven orthopaedic patients (11.9%) had MINS. MINS was associated independently with 30-day mortality including among those who had had orthopaedic surgery. Orthopaedic patients without and with MINS had a 30-day mortality rate of 1.0% and 9.8%, respectively (odds ratio [OR], 11.28; 95% confidence interval [CI], 6.72 to 18.92). The 30-day mortality rate was increased for patients with MINS who had an ischemic feature (i.e., symptoms, or evidence of ischemia on electrocardiography or imaging) (OR, 18.25; 95% CI, 10.06 to 33.10) and for those who did not have an ischemic feature (OR, 7.35; 95% CI, 3.37 to 16.01). The proportion of orthopaedic patients with MINS who were asymptomatic and in whom the myocardial injury would have probably gone undetected without TnT monitoring was 81.3% (95% CI, 76.3% to 85.4%). Conclusions: One in 8 orthopaedic patients in our study had MINS, and MINS was associated with a higher mortality rate regardless of symptoms. Troponin levels should be measured after surgery in at-risk patients because most MINS cases (>80%) are asymptomatic and would go undetected without routine measurements. Level of Evidence: Prognostic Level II . See Instructions for Authors for a complete description of levels of evidence.